Distinguishing papillary endothelial hyperplasia and angiosarcoma on core needle biopsy of the breast: The importance of clinical and radiologic correlation. Issue 4 (24th February 2018) - Guilbert, Marie‐Christine; Frost, Elisabeth P.; Brock, Jane E.; Lester, Susan C.
Abstract: Papillary endothelial hyperplasia (PEH) is a rare non‐neoplastic exuberant organizing hematoma that can closely mimic angiosarcoma due to a resemblance to malignant anastomosing blood vessels. It could be particularly difficult to distinguish PEH from angiosarcoma in breast core needle biopsies. We identified all cases of these lesions diagnosed on core needle biopsy in order to identify clinical, radiologic, and pathologic features that could prove helpful to arrive at the correct diagnosis. Four cases of PEH and 4 cases of angiosarcoma were identified. The mean age at diagnosis was 62 for PEH and 33 for primary angiosarcoma. All cases of PEH formed small masses with circumscribed or lobulated margins by imaging (mean size 0.9 cm). In 3 cases, the masses were difficult or impossible to identify after the biopsy. Angiosarcomas presented as larger masses with ill‐defined margins (mean size 2.8 cm) that were unchanged in size after biopsy. PEH was surrounded by adipose tissue, whereas angiosarcoma invaded into fibrous stroma and involved lobules. The pseudopapillary structures of PEH were composed mainly of collagen, and thus, additional histologic stains for fibrin were not helpful for diagnosis. The 4 patients with PEH received no further treatment and are alive and disease‐free at 2‐11 years of follow‐up. In contrast, the patients with angiosarcoma underwent mastectomy and chemotherapy or radiation therapy. Two of the patients with angiosarcoma died 3 years after diagnosis and the other 2 patients are alive without disease at 5 and 6 years. Therefore, distinguishing PEH and angiosarcoma is essential for appropriate management. This is the first series to compare these lesions on core needle biopsy and the first to note important clinical, imaging, and histologic differences that aid in making a diagnosis of PEH with confidence on breast core needle biopsy.